Espaços não formais na formação do professor de matemática: uma análise a partir do Núcleo de Ações Educativas da UnU de Goiás/UEG -NEMENF - Daude, Rodrigo Bastos (2014)
This dissertation is part of the Master degree in Education in Science and Mathematics from the research program of Universidade Federal de Goiás, and aims to examine the pedagogical potential of using non-formal spaces in teacher training of math, in Goiás city. It understands the realization that the formation of the licensee math should not be tied to a single methodology, and the need to meet the different learning processes. For that teacher training should address these differences and take place in multiple spaces. In this perspective, we seek to answer: How do the activities at the Center for Educational Activities: Mathematics Education in Non-Formal Spaces -NEMENF changes the design of the participants regarding the use of non-formal spaces in teacher training in mathematics? For this we present historical, educational and legal aspects in teacher from the LDB (1996), authors like Gatti (2010), Saviani, Curi (2000), D'Ambrosio (2001, 2003) and Fiorentini (1994 , 1995). At the same time, we present the non-formal spaces methodological pluralist perspective in approaching a mathematical education contextualized in Trilla (1996), Sarramona (1998) and Gohn (2006, 2010). The outline of the research was conducted in the course of degree in Mathematics from the Universidade Estadual de Goiás, Campus Goiás within a group of studies on the subject. In developing the survey was necessary to use a qualitative approach in the midst of a collaborative case study in which all subjects can express opinions and hypotheses to be investigated. Partly realized by resorting to issues of culture, everyday life and teaching contextualized increase the chances of success in teaching and learning. And the non-formal spaces contribute significantly in this task, from two perspectives: the teaching of scientific knowledge and educational background generated in the process of social participation.